2014
DOI: 10.1186/1471-244x-14-172
|View full text |Cite
|
Sign up to set email alerts
|

The addition of STEPPS in the treatment of patients with bipolar disorder and comorbid borderline personality features: a protocol for a randomized controlled trial

Abstract: BackgroundBipolar disorder (BD) and borderline personality disorder (BPD) both are severe and chronic psychiatric disorders. Both disorders have overlapping symptoms, and current research shows that the presence of a BPD has an adverse effect on the course of BD. The limited research available shows an unfavorable illness course, a worse prognosis and response to medication, longer treatment duration, more frequent psychiatric admissions, higher drop-out, increased risk of substance abuse, increased risk of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…STEPPS has also been studied in forensic groups, such as prisoners with BPD, and findings showed that STEPPS resulted in reductions in BPD severity with a large effect size from baseline to the end of treatment (Black, Blum, McCormick, & Allen, 2013). STEPPS has been tested in the treatment of bipolar disorder and comorbid personality features (Reimann et al, 2014).…”
mentioning
confidence: 99%
“…STEPPS has also been studied in forensic groups, such as prisoners with BPD, and findings showed that STEPPS resulted in reductions in BPD severity with a large effect size from baseline to the end of treatment (Black, Blum, McCormick, & Allen, 2013). STEPPS has been tested in the treatment of bipolar disorder and comorbid personality features (Reimann et al, 2014).…”
mentioning
confidence: 99%
“…Riemann et al reported that bipolar disorder patients with comorbid BPD are more likely to be hospitalized and have an increased risk of substance abuse [8]. As per the National Comorbidity Survey Replication, the prevalence of alcohol abuse and drug abuse in bipolar patients is 39.1% and 28.8% respectively [3].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of comorbid BPD had a negative impact on the clinical course of bipolar disorder as the patients had an unfavorable illness trajectory, higher likelihood of hospitalization, longer treatment duration and worse response to treatment [7]. Riemann et al concluded from a study in a multicenter outpatient that bipolar patients with BPD had a higher treatment drop-out rate, increased risk of substance abuse, and greater impairment of social and occupational functioning [8]. As bipolar disorder and BPD are each risk factors for suicidal behavior, patients with co-occurring bipolar disorder and BPD present with a higher suicide risk [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent treatment protocol involved an RCT of a psychotherapeutic treatment versus treatment as usual for bipolar disorder (Riemann et al, 2014), andMcDermid andMcDermid (2016), argued comorbid BP/BPD resulted in 'emotional frailty' and diminished 'complexity' -and recommended developing sufficient complexity through targeting internal coping strategies while utilising external psychological supports to develop optimal emotional reactivity. Parker (2015) has advocated a two-tier approach to treatment for those with comorbid BP/BPD -the first step involving treating the bipolar illness predominantly with a mood stabilising agent and then addressing the BPD with a psychotherapy.…”
Section: Comorbid Bp/bpd Vs Bpd Vs Bp Comparisonsmentioning
confidence: 99%